The The Effect of Katuk Vegetable Feeding on Breast Milk Production at TPMB Mimik Suwarminingsih, Mumbulsari District, Jember Regency - Perbawati, Dinar; Pripuspitasari, Dini Eka; Yuningsih, Yuningsih (Puslitbang Sinergis Asa Professional, 2025)
Suboptimal exclusive breastfeeding coverage remains a significant health challenge. Non-pharmacological interventions are needed to support lactation. Katuk (Sauropus androgynus) leaves are traditionally known as a natural galactagogue due to their bioactive compounds that stimulate prolactin and oxytocin, but empirical evidence on their efficacy during the critical early postpartum period is limited. Objective: This study aimed to analyze the effect of katuk leaf consumption on breast milk production in postpartum mothers, measured through infant weight gain. This study utilized a one-group pre-experimental design with a pretest-posttest approach. A total of 16 postpartum mothers were recruited through purposive sampling. The intervention consisted of consuming 200 grams of steamed katuk leaves daily for seven consecutive days. Infant weight was measured before the intervention (Day 4) and after (Day 8) to assess breast milk production adequacy. Data were analyzed using the Wilcoxon Signed-Rank Test. Results: The findings revealed a statistically significant increase in infant weight gain post-intervention. The median infant weight gain rose from 110g at pretest to 190g at posttest. The Wilcoxon Signed-Rank Test confirmed that this improvement was significant (Z = -3.527, p = 0.001). The consumption of katuk leaves is significantly associated with increased breast milk production among postpartum mothers. This supports its potential as an accessible and non-pharmacological intervention to enhance lactation. However, due to the study's pre-experimental design without a control group, these findings should be interpreted with caution. Further research using randomized controlled trials is recommended to establish causality.